التأمين على الودائع كالية لتحفيز العملاء على التعامل مع البنوك التجارية في الجزائر - ابتسام, واغد; مسعودة, عليه; أمل, طبية (University of eloued جامعة الوادي, 2021)
نهدف من خلال هذه المذكرة إلى تبيان أهمية التأمين على الودائع البنكية، وإن كثرة إيداع الودائع البنكية من طرف المدخرين ماهي إلا دليل على ثقتهم في القطاع المصرفي وهذه الثقة تجعل البنوك التجارية في سعي دؤوب من أجل الحفاظ على الثقة وذلك عن طريق إيجاد العديد من الحلول لتعويض هؤلاء العملاء في حابة حدوث أزمة أو مشكلة، ومن بين هذه الحلول أنظمة التأمين على الودائع الودائع البنكية وآلية لتحفيز العملاء على التعامل مع البنوك التجارية، بحيث يعتبر نظام تأمين على الودائع آلية لتحفيز العملاء على التعامل مع البنوك التجارية في الجزائر من اجل الحفاظ على استقرار القطاع المصرفي، ولقد تم تبني نظام التأمين على الودائع البنكية في الجزائر فعلا سنة 2003، على إثر إفلاس البنكين الخاصين "بنك الخليفة والبنك التجاري والصناعي"، بحيث توصلنا إلى أن نظام التأمين على الودائع البنكية في الجزائر لا يلعب دورا كبيرا في تحقيق الاستقرار المالي لأن أغلبية البنوك عمومية أي لا تتعرض لإفلاس. We aim through this note to show the importance of insurance on bank deposits، and that the large number of deposits of bank deposits by some of the savers is only evidence of their confidence in the banking sector and this confidence makes commercial banks in a relentless quest to maintain this confidence by finding many Solutions to compensate these customers in the event of a crisis or problem، and among these solutions are bank deposit insurance systems as a mechanism to motivate customers to deal with commercial banks، so that the bank deposit insurance system is considered a mechanism to motivate customers to deal with Algerian commercial banks in order to maintain stability The banking sector، and the bank deposit insurance system in Algeria was actually adopted in 2003، following the bankruptcy of the two private banks “the Khalifa Bank and the Commercial and Industrial Bank”، so we concluded that the bank deposit insurance system in Algeria does not play a major role in achieving financial stability. Because the majority of banks are public، that is، they are not exposed to bankruptcy.
ماستر اقتصاد
Keywords: المخاطر البنكية، التأمين على الودائع البنكية، نظام التأمين على الودائع البنكية في الجزائر.; Banking risks, insurance, bank deposit insurance systems, bank deposit insurance.